(untitled) (Research, Society and Development, 2022)
Propolis is a viscous product produced and collected by worker bees from shots or plant exudates used for the protection of hive. The aims of this work were to perform the phytochemical profile and biological activity of propolis from stingless bee (SB) Melipona quadrifasciata (Mandaçaia) native from Rio Grande do Sul, Brazil. The propolis had a total phenolic concentration of 126,52 mg g-1, and the major phenolic compounds identified were p-coumaric acid (35,64 mg g-1) and gallic acid (18,33 mg g-1). The carotenoids β-carotene, β-criptoxanthin, lutein and lycopene were identified in the propolis of M. quadrifasciata, and β-carotene showed the highest concentration (1.56 mg/100g). The headspace analysis of volatile compounds identified the highest concentration of α-pinene, followed by limonene, sylvestrene and β-pinene. The propolis of M. quadrifasciata showed high antioxidant activity by the DPPH method, with EC50 of 2,29 µg mL-1, antimicrobial activity (MIC) against Escherichia coli and Staphylococcus aureus and low reduction in cell viability of cell lines L929, GL, A549, MDA and SKMEL.